2017
DOI: 10.1097/iae.0000000000001461
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Pupillary Capture After Vitrectomy and Transscleral Fixation of an Intraocular Lens

Abstract: Concurrent iridotomy using a vitreous cutter probe is an easy, rapid, and effective procedure to prevent possible pupillary capture after combined vitrectomy and transscleral fixation of intraocular lens implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In previous studies about sutured scleral fixation, the complication rates of IOL capture were reported up to 30%. 13,14 The other studies assessing alternative sutured scleral fixation methods using Gore-Tex have reported complication rates of IOL tilt up to 45%. [15][16][17] However, most studies have reported good centration of IOL and pupillary capture was resolved spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies about sutured scleral fixation, the complication rates of IOL capture were reported up to 30%. 13,14 The other studies assessing alternative sutured scleral fixation methods using Gore-Tex have reported complication rates of IOL tilt up to 45%. [15][16][17] However, most studies have reported good centration of IOL and pupillary capture was resolved spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no recurrence of pupillary optic capture occurred after IOL repositioning with postoperative pilocarpine 2.0%. Kim et al 22 reported that peripheral iridotomy helped to prevent pupillary capture after conventional sutured scleral fixation. However, in this study, peripheral iridotomy sites were constructed in all cases, and they did not completely prevent pupillary optic capture.…”
Section: Discussionmentioning
confidence: 99%